Carers' experience of using assistive technology for dementia care at home: a qualitative study. Issue 3 (18th March 2020) - Sriram, Vimal; Jenkinson, Crispin; Peters, Michele
Abstract : Objective: Assistive technology (AT) can help carers (family, friends and neighbours) and people with dementia to stay well and safely at home. There are important gaps in what we know about experience of using AT from the perspective of carers of persons with dementia. This study investigates carers' experience of using AT in supporting and caring for persons with dementia who live at home. Design: Qualitative phenomenological study with semi-structured interviews to achieve data saturation and thematic analysis to identify key themes. Setting: Community-based within the UK. Participants: Twenty-three (14 women, 9 men) adult carers of persons with dementia who have used at least one AT device. Results: All participants reported benefiting to varying degrees from using AT. There were 5 themes and 18 subthemes that highlighted reasons for using AT and use of AT over time. Providing care for a person with dementia, motivation for using AT, changes to roles and routines, carer knowledge and skills for using AT and social, environmental and ethical considerations were the main themes. This study showed that AT can provide reassurance and support for carers of persons with dementia but there are difficulties with acquiring and continued use of AT as dementia progresses. Conclusions: Carers consider AT as an adjunct to care they provided in caring for a person with dementia. Use of AT should be considered in the personal, social and environmental context of persons with dementia and their carers. Further research and policy interventions are needed to address best use of resources and guidance on data sharing and data protection while using AT.